Comparative evaluation of economic effi ciency of modern inhaled anesthetics - D. Yu. Belousov; E. V. Afanasyeva; E. A. Efremova (Качественная клиническая практика, 2018)
The purpose of presented retrospective analysis was to identify retrospectively and estimate the economic benefits that can occur when comparing the costs of using desflurane or sevoflurane for anesthesia during surgery. Formalization and evaluation were carried out in accordance with the industry standard “Health technology assessment”, approved and signed into law June 14, 2014 by Order of the Federal Agency for Technical Regulation and Metrology of the Russian Federation GOST №568-art and ISPOR recommendations, and meet the requirements of statistical significance, allowing to develop recommendation conclusions on the use of each product in any given situation. Pharmacoeconomic evaluation is based on data from official registration licenses and patient information leaflets, randomized controlled clinical trials data and information on value, pricing and costs obtained from the public independent sources. In accordance with the objectives, indications and limitations on the use of these drugs for anesthesia, the target population of this study were patients of diff erent ages, who required the use of inhalation anesthesia during the ongoing surgical procedures: patients with physiological status not higher than Class I (ASA I) on the scale of the American Association of Anesthesiologists. Compared medical technologies were III generation inhalation analgesics Sevorane and Suprane. Th ere was conducted a cost-effectiveness analysis of the inhalation anesthetics, during which cost of achieving the minimum alveolar concentration (MAC) using compared inhaled anesthetic drugs was estimated. The analysis showed that the difference in favor of desflurane is 155.72 rub for a four-hour operation. The most significant influence on the direct medical costs associated with the use of inhalation anesthesia was shown by the cost of inhalation anesthetic (gas) per 1 ml, the concentration of the gas, the flow rate of fresh gas, duration of anesthesia. Sensitivity analysis confirmed the data obtained. In the current situation of the retrospective evaluation the assumed shift from sevoflurane to desflurane in 1 000 patients aged 12 to 60 years that require inhalation anesthesia, will be accompanied by cost savings of 102,907 rub to 155,720 rub, and with the use of induction of anesthesia with propofol up to 162 900 rub. Whereas during anesthesia in newborns and patients older than 60 years shift of desflurane to sevoflurane in 1 000 patients will reduce the cost by 266,354 rub and 225,672 rub respectively. Therefore the economic benefit from the use of a single inhalation anesthetic both as an induction drug and as a drug anesthetic drug has not been proved clinically and from an economic point of view that may require individual assessment of costs on the basis of regions of the Russian Federation or a particular institution.